Effect of direct-acting antivirals for hepatitis C virus-related hepatocellular carcinoma recurrence and death after curative treatment - Ahn, Young-Hwan; Lee, Heirim; Han, Ji Eun; Cho, Hyo Jung; Cheong, Jae Youn; Park, Bumhee; Kim, Soon Sun (Journal of liver cancer, 2022)
Background/Aim: There has been a long-standing debate about the association of directacting antiviral (DAA) therapy and hepatocellular carcinoma (HCC) recurrence. This study aimed to investigate the association between DAA therapy and HCC recurrence after curative therapy.Methods: We retrospectively enrolled 1,021 patients with HCV-related (hepatitis C virus) HCC who underwent radiofrequency ablation (RFA), liver resection, or both as the first treatment modality from January 2007 to December 2016 and without a history of HCV therapy before HCC treatment from a nationwide database. The effect of HCV treatment on HCC recurrence and all-cause mortality was also investigated.Results: Among the 1,021 patients, 77 (7.5%) were treated with DAA, 14 (1.4%) were treated with interferon-based therapy, and 930 (91.1%) did not receive HCV therapy. DAA therapy was an independent prognostic factor for lower HCC recurrence rate (hazard ratio [HR], 0.04; 95% confidence interval [CI], 0.006-0.289; P=0.001 for landmarks at 6 months after HCC treatment and HR, 0.05; 95% CI, 0.007-0.354; P=0.003 for landmarks at 1 year). Furthermore, DAA therapy was associated with lower all-cause mortality (HR, 0.049; 95% CI, 0.007-0.349; P=0.003 for landmarks at 6 months and HR, 0.063; 95% CI, 0.009-0.451; P=0.006 for landmarks at 1 year).Conclusions: DAA therapy after curative HCC treatment can decrease HCC recurrence and all-cause mortality compared to interferon-based therapy or no antiviral therapy. Therefore, clinicians should consider administering DAA therapy after curative HCC treatment in patients with HCV-related HCC.